Thai hotel undergraduate interns’ awareness and attitudes towards English as a lingua franca - Suebwongsuwan, Waraporn; Nomnian, Singhanat (Indonesian Journal of Applied Linguistics, 2020)
The study examines twenty-eight Thai undergraduate hotel interns’ attitudes towards the use of English as a lingua franca (ELF) in terms of its varieties of spoken English. Drawing upon the questionnaire, semi-structured interview, and verbal-guise test based on the eleven recorded voices whose accents obtained were from native and non-native speakers, the findings reveal that the students reflected the most positive attitudes towards American and Hong Kong accents while the Korean one was rated rather negatively. However, the students were well aware of the lingua franca status of their spoken English; and thus, the non-native accents were tentatively accepted. This study suggests that Thai leaners’ awareness and positive attitude towards varieties of English must be promoted in both English classes and on-the-job training. English teachers and trainers of hotel staff should also be aware of the significance of exposure to accents and introduce undergraduate interns to varieties of English in order to enhance mutual intelligibility for effective ELF communication at work.